Perception of Competency-Based Medical Education (CBME) Among MBBS Students: A Cross-Sectional Study in Two Indian Medical Colleges - Bhati, Jai; Tanya, Tanya; Saini, Kashish; Jagnani, Prachi; Aastha, Aastha; Yadav, Kanav; Kumar Garg, Hemant; Mohan, Col. Brij (Journal of Neonatal Surgery, 2025)
Background: Competency-Based Medical Education (CBME) was introduced in India in 2019 to produce Indian Medical Graduates (IMGs) equipped with essential knowledge, skills, ethics, and communication. Understanding student perception is vital for successful implementation. Objectives: To assess awareness, perceived benefits, challenges, and overall satisfaction with CBME among MBBS students and interns. Methods: A cross-sectional study was conducted among 200 participants (150 MBBS students and 50 interns) from two Indian medical colleges. A 15-item Likert scale questionnaire was used. Data were analyzed using descriptive statistics and visualized through pie charts, line diagrams, box plots, and scatter graphs. Results: 78% of students were aware of CBME; 42% could define its principles. 65% agreed CBME improved clinical skills; 72% appreciated early clinical exposure. 60% reported increased workload; 55% found assessments unclear. Overall satisfaction was moderate, with 55% satisfied, 25% neutral, and 20% dissatisfied. Conclusion: Students recognize CBME’s value but face challenges in workload and assessment clarity. Faculty development and student orientation are essential for optimizing CBME delivery.